Using GPS Data to Study Neighborhood Walkability and Physical Activity - Rundle, Andrew G.; Sheehan, Daniel M.; Quinn, James W.; Bartley, Katherine; Eisenhower, Donna; Bader, Michael M.D.; Lovasi, Gina S.; Neckerman, Kathryn M. (American journal of preventive medicine, 2016)
Urban form characteristics intended to support pedestrian activity, collectively referred to as neighborhood walkability, are thought to increase total physical activity. However, little is known about how neighborhood walkability influences utilization of neighborhood space by residents and their overall physical activity. Sociodemographic information and data on mobility and physical activity over 1-week periods measured by GPS loggers and accelerometers were collected from 803 residents of New York City between November 2010 and November 2011. Potentially accessible neighborhood areas were defined as land area within a 1-kilometer distance of the subject’s home (radial buffer) and within a 1-kilometer journey on the street network from the home (network buffer). To define actual areas utilized by subjects, a minimum convex polygon was plotted around GPS waypoints falling within 1 kilometer of the home. A neighborhood walkability scale was calculated for each neighborhood area. Data were analyzed in 2014. Total residential neighborhood space utilized by subjects was significantly associated with street intersection density and was significantly negatively associated with residential density and subway stop density within 1 kilometer of the home. Walkability scale scores were significantly higher within utilized as compared with non-utilized neighborhood areas. Neighborhood walkability in the utilized neighborhood area was positively associated with total weekly physical activity (32% [95% CI=17%, 49%] more minutes of moderate-equivalent physical activity across the interquartile range of walkability). Neighborhood walkability is associated with neighborhood spaces utilized by residents and total weekly physical activity.